Role of Gate Type in the Air-Demand Ratio in Closed Conduits - Aydin, A. B.; Baylar, A.; Ozkan, F.; Tuna, M. C.; Ozturk, Mualla (Sciendo, 2024)
Sluice and radial gates are common devices used to control flow in closed conduits. In high-head gated conduits, the high-velocity flow exiting the gate drags and entrains a lot of air. If the air demand of the flow is not met, the pressure drop downstream of the gate will cause structural damage or cavitation. Typically, an air vent is installed immediately downstream of the gate to supply sufficient air to the flow. In this study, the effect of the conduit gate type on the air-demand ratio was investigated. The results showed that the gate type had a very significant effect on the air-demand ratio. Significantly higher air-demand ratios were observed in the conduit with a sluice gate compared to the conduit with a radial gate. The results obtained will be useful in future modeling and design processes.
Keywords: air-water flow; cavitation; gate; high-head flow; high-velocity flow